Hubungan Pre-Eklampsia Dengan Angka Kejadian Seksio Sesaria - Andi Syintha Syintha Ida; Nurjaya Nurjaya; Andi Ika Abriani (POLTEKKES KEMENKES MANADO, 2021)
Background: Pre-eclampsia is one of the factors causing high maternal and infant mortality rates, especially in developing countries such as Indonesia and this will continue to increase if efforts to prevent not being qualified and professional, one of the treatments of pre-eclampsia is the act of Cesarean section which for medical personnel is the main choice to save the mother and fetus, because longer delays in delivery will cause serious harm to the mother, fetus or. Purpose: toknow the relationship of Pre-eclampsia with the number of incidents Cesarean section Method: Design analytical observational research with a cross sectional approach. Sampling technique is accidental sampling with the number of samples as many as 40. The results showed that of 40 respondents there were 35 (87.5%) who had pre-eclampsia and 5 (12.5%) who had severe pre-eclampsia. Based on the results of the statistical test, the value p = 0.005 < α = 0.05. There is a significant relationship between the incidence of Pre-eclampsia and the incidence of Cesarean section in RSUP Dr.Wahidin Sudirohusodo Makassar in 2018 Keywords: Pre-eclampsia Relationship, Cesarean section